On-demand chlorine dioxide solution enhances odontoblast differentiation through desulfation of cell surface heparan sulfate proteoglycan and subsequent activation of canonical Wnt signaling - Inubushi, Toshihiro; Priyanka, Nag; Watanabe, Masakatsu; Takahashi, Yusuke; Kusano, Shinnosuke; Kurosaka, Hiroshi; Papagerakis, Silvana; Papagerakis, Petros; Hayashi, Mikako; Yamashiro, Takashi (Frontiers in Cell and Developmental Biology, 2023)
Heparan sulfate proteoglycans (HSPGs) surround the surface of odontoblasts, and their modification affects their affinity for Wnt ligands. This study proposes applying Matching Transformation System® (MA-T), a novel chlorinated oxidant, to enhance dentinogenesis. MA-T treatment in odontoblasts decreased sulfation of HSPG and upregulated the expression of dentin sialophosphoprotein (Dspp) and Dentin Matrix Protein 1 (Dmp1) via activation of canonical Wnt signaling in vitro. Ex vivo application of MA-T also enhanced dentin matrix formation in developing tooth explants. Reanalysis of a public single-cell RNA-seq dataset revealed significant Wnt activity in the odontoblast population, with enrichment for Wnt10a and Wnt6. Silencing assays showed that Wnt10a and Wnt6 were redundant in inducing Dspp and Dmp1 mRNA expression. These Wnt ligands’ expression was upregulated by MA-T treatment, and TCF/LEF binding sites are present in their promoters. Furthermore, the Wnt inhibitors Notum and Dkk1 were enriched in odontoblasts, and their expression was also upregulated by MA-T treatment, together suggesting autonomous maintenance of Wnt signaling in odontoblasts. This study provides evidence that MA-T activates dentinogenesis by modifying HSPG and through subsequent activation of Wnt signaling.